Creating motion graphics with after effects. - Meyer, Trish, ....-; Meyer, Trish and Chris, ....-; Meyer, Chris, ....- (San Francisco : CMP, 2002)
Samenvatting:Master all the core concepts needed to use After Effects 5.5 on a dailybasis, including transformations, keyframing animation, editing layers,masking, track mattes, stencils, nesting, precomposing, transfer modes,effects, adjustment layers, and rendering, plus the major new featuresParenting, 3D Layers, Cameras, and Lights. In addition to the new topics,owners of the first edition of CMG will benefit from the updated coverageof such key features as transfer modes, masking, and collapsingtransformations. Beginners and students will enjoy the new first chapter,which takes them on a tour through After Effects in the form of creatinga mythical television show opening title sequence. The CD includes freeplug-ins and keyframe assistants from Boris FX, Walker Effects, DigitalFilm Tools, The Foundry, Digital Anarchy, and DigiEffects plusinspirational footage from Artbeats, Digital Vision, and EyeWire toexperiment with.
2: Advanced techniques. CD-rom included
Keywords: Webdesign